2023
DOI: 10.3390/cells12182230
|View full text |Cite
|
Sign up to set email alerts
|

New High-Affinity Thrombin Aptamers for Advancing Coagulation Therapy: Balancing Thrombin Inhibition for Clot Prevention and Effective Bleeding Management with Antidote

Mohamad Ammar Ayass,
Natalya Griko,
Victor Pashkov
et al.

Abstract: Thrombin is a key enzyme involved in blood clotting, and its dysregulation can lead to thrombotic diseases such as stroke, myocardial infarction, and deep vein thrombosis. Thrombin aptamers have the potential to be used as therapeutic agents to prevent or treat thrombotic diseases. Thrombin DNA aptamers developed in our laboratory exhibit high affinity and specificity to thrombin. In vitro assays have demonstrated their efficacy by significantly decreasing Factor II activity and increasing PT and APTT times in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Reduced APTT is associated with increased risk of VTE occurrence, [ 26 , 27 ] the data of this study also shows that the PT ( P = .041), APTT ( P = .040) is significantly higher than that of female patients, indicating that the coagulation levels of these male patients are significantly higher than those of female patients, may be related to the use of anticoagulants. [ 28 , 29 ] The clinical use of D-dimer testing in anticoagulated patients is very limited, [ 30 ] but D-dimer enhances thrombus risk in cancer patients, [ 31 ] blood biochemical analysis data showed that female patients had higher but not significant D-dimer than male patients ( P = .739), and C-reactive protein was significantly less than male patients ( P = .032). Creatinine and urea level can serve as an indicator of renal function, [ 32 ] and an increase in blood urea nitrogen/creativity ratio may be related to an increased risk of VTE, [ 33 ] the data of this study showed that male patients had higher creatinine( P < .001) and urea ( P < .005) level than female patients, data from blood gas analysis showed that PaO 2 ( P = .034) and K + ( P = .010) was significantly higher in male patients than in female patients, considering the preventive effect of non-vitamin K antagonist oral anticoagulants on VTE, [ 34 , 35 ] we speculate that higher blood potassium levels in males are also one of the reasons for their higher incidence of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced APTT is associated with increased risk of VTE occurrence, [ 26 , 27 ] the data of this study also shows that the PT ( P = .041), APTT ( P = .040) is significantly higher than that of female patients, indicating that the coagulation levels of these male patients are significantly higher than those of female patients, may be related to the use of anticoagulants. [ 28 , 29 ] The clinical use of D-dimer testing in anticoagulated patients is very limited, [ 30 ] but D-dimer enhances thrombus risk in cancer patients, [ 31 ] blood biochemical analysis data showed that female patients had higher but not significant D-dimer than male patients ( P = .739), and C-reactive protein was significantly less than male patients ( P = .032). Creatinine and urea level can serve as an indicator of renal function, [ 32 ] and an increase in blood urea nitrogen/creativity ratio may be related to an increased risk of VTE, [ 33 ] the data of this study showed that male patients had higher creatinine( P < .001) and urea ( P < .005) level than female patients, data from blood gas analysis showed that PaO 2 ( P = .034) and K + ( P = .010) was significantly higher in male patients than in female patients, considering the preventive effect of non-vitamin K antagonist oral anticoagulants on VTE, [ 34 , 35 ] we speculate that higher blood potassium levels in males are also one of the reasons for their higher incidence of VTE.…”
Section: Discussionmentioning
confidence: 99%